Behaviour of TiC Particles on the Co50-Based Coatings by Laser Cladding: Morphological Characteristics and Growth Mechanism - Nga Thi-Hong Pham; Van-Thuc Nguyen (Advances in Materials Science and Engineering)
H13 steel surfaces are covered by coatings of Co-based alloy with 0, 10, 20, and 30 wt. % TiC using the laser cladding (LC) method. The morphological characteristics, growth mechanism, and the mechanical properties of TiC on the microstructure of the coatings were studied. The results show that TiC in the TiC/Co50 composite coating is composed of two parts: incompletely melted TiC and in situ TiC. TiC content has a great effect on the morphology of TiC, and it exists in different shapes: original TiC, fine-particle TiC, segregated TiC, petal-shaped TiC, and branch-shaped TiC. Additionally, the morphology of TiC in different areas of the coating is different, while TiC size gradually increases from bonding zone to surface. In the 10% TiC+Co50 coating, TiC mainly appears as undermelted, fine particles, precipitates, and having shapes of polygons and petals. From the bottom of this coating, the number of petal-shaped TiC has increased, and the particle size is also enlarged. In the 20% TiC+Co50 coating, the TiC in the coating mainly presents as undermelted, fine particles, and dendritic morphology. From the bottom of this coating to the surface, the particle size of the undermelted TiC shows a clear gradient change. Finally, the 30% TiC+Co50 coating does not have in situ TiC, and there is no obvious gradient change in the particle size of undermelted TiC. After coating by the LD method, the surface hardness is strongly enhanced. The average hardness of Co50 alloy, Co+10% TiC, and Co+20% TiC composite coatings is 499 HV0.2, 552 HV0.2, 590 HV0.2, and 824 HV0.2, respectively. These values are 2.4–4.0 times harder than that of the H13 substrate. The wear resistance of Co50 alloy, Co+10% TiC, and Co+20% TiC composite coatings is greatly higher than that of H13 steel, showing excellent wear characteristics. The friction coefficient of the coatings which have TiC is very stable. Therefore, the coatings can satisfy the requirement of tool steels applications. Additionally, the wear mechanism of the coating at room temperature is mainly brittle spalling, adhesive, and ploughing. At 700°C, the wear mechanism is mainly oxidation and fatigue.